Corrosion stability of molybdenum and tungsten coatings in lead-bismuth eutectic - Azhazha, V.M.; Bakai, A.S.; Glushko, P.I.; Kovtun, K.V.; Omelchuk, A.A.; Semenov, N.A.; Skryptun, I.N.; Sheremet, V.I.; Shirokov, B.M.; Shmegera, R.S. (Вопросы атомной науки и техники, 2005)
The paper presents results of corrosion tests of tungsten- and molybdenum-based protective coatings, deposited on nickel-molybdenum alloys (hastelloy) in heavy metal melts (Pb, Bi, Pb–Bi eutectic). Results of an investigation of hastelloy samples without protective coating are given for comparison. The investigations were carried out under static conditions at 550 °C. The mechanical properties of the samples under investigation have been shown that the corrosion stability of the uncoated alloys studied decreases in the order: lead – lead-bismuth eutectic – bismuth. The use of protective tungsten and molybdenum coatings ensures corrosion stability of hastalloy with retention of its mechanical properties.